The Transformation of News Editors After the Use of Artificial Intelligence (AI) Technology - Ana Noviani; Agnes Yusuf; Dedi Prasetia; Siti Retno Wulandari (Pelopor Publikasi Akademika, 2026)
This research explores the use of artificial intelligence (AI) technology in newsroom environments and its impact on the behavioral changes of journalists, particularly at the news editor level. The adoption of generative AI in mass media continues to grow in line with the rapid advancement of digital technology globally. The application of AI in journalistic work—such as news gathering, writing, editing, and distribution—has had significant effects on media professionals. This research aims to examine in depth news editors' perspectives on the use of AI in the newsroom and the behavioral transformations that result from it. The study adopts an interpretive paradigm, with a qualitative approach and Interpretative Phenomenological Analysis (IPA) as its research strategy. It uses concepts from technological determinism, diffusion of innovations theory, and journalistic ethics as analytical tools to better understand the phenomena experienced by the research participants. The findings reveal three key aspects of transformation among news editors following the integration of AI in newsroom practices: changes in work routines, the meaning attributed to AI in journalism, and the evolving competencies of news editors. AI technology is viewed as a supporting tool rather than a replacement for news editors. While technical functions such as writing SEO-based articles, checking language structure, and conducting issue research can be performed by AI, editorial decisions and final editing remain the responsibility of human editors. In conclusion, the study highlights news editors' responses and interpretations of AI use, with their transformation marked by increased work efficiency.